The Fox from Bajiazui (Qingyang, Central China) and an Update on Early Pleistocene Foxes from China - Saverio Bartolini-Lucenti; Qigao Jiangzuo; Hao Jiang; Zhaoyu Li; Kun Xie; Joan Madurell-Malapeira (Quaternary, 2023)
(1) Background: despite the fact that nowadays the genus Vulpes Frisch, 1775, is the most diverse among extant Canidae, its fossil record is utterly scarce, especially in the Asian Pliocene. The sparse nature of this record further complicates the reconstruction of the evolutionary scenario to fit these taxa with extant species. The situation seems to change slightly in the Early Pleistocene when two species are recorded: Vulpes alopecoides (Del Campana, 1913) in Europe and Vulpes chikushanensis, Young, 1930, in Asian localities. Unlike the former, which has an extensive record, the remains of the Chinese V. chikushanensis are sporadic and the validity of the taxon has also been questioned. (2) Methods: the study of the specimens from the Early Pleistocene site of Bajiazui (1.8–1.2 Ma, Qingyang, Gansu) in comparison to an extensive sample of Vulpes spp. The Pliocene–Early Pleistocene is relevant for the delimitation of fossil foxes variability; (3) Results: morphologically and morphometrically, the specimens of Bajiazui fit with the specimens of V. chikushanensis from other Chinese localities of the Early Pleistocene, e.g., Longdan (Gansu) and Huiyu (Fangshang), highlighting some difference with the latest Early Pleistocene forms of Jigushan fox; (4) Conclusions: the revision of the Asian fossil record of Vulpes is crucial in our attempt to understand and reconstruct the evolution of carnivoran guild during the late Early Pleistocene (1.8–0.8 Ma). The fox remains from Bajiazui, although fragmentary, add a valuable piece to our knowledge of V. chikushanensis, a species possibly strongly related to the extant Vulpes corsac (Linnaeus, 1768).